Factors Affecting Taxpayer Compliance Kpp Pratama Candisari Indonesia - Rr. Suprantiningrum; Paramithaningtyas, Dimas Ajie (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study aims to analyze the effects of e-TPS implementation, taxpayer awareness, service quality, and taxpayer awareness and understanding of compliance The population of this study are all registered taxpayers of KPP Pratama Semarang Candisari The sample for this study consisted of individual taxpayers who met with up to 70 respondents at the Pratama Semarang Candisari tax services office. The data used in this study are raw data collected through questionnaires and analyzed using SPSS software Data were analyzed using multiple linear regression analysis to test hypotheses. The results of this study show that: (1) The application of e-SPT has a significant positive impact on taxpayer compliance (2) Raising taxpayer awareness has a significant positive impact on taxpayer compliance (3) Service quality has a significant positive impact on taxpayer compliance (4) Taxpayer knowledge and understanding has a significant positive impact on taxpayer compliance.